Anterior segment optical coherence tomography findings of iris granulomas in Hansen's disease: a case report - Mahendradas, Padmamalini (Springer, 2013)
BACKGROUND: A 50-year-old male was diagnosed to have a right eye sclerouveitis and left eye granulomatous anterior uveitis due to Hansen's disease. We are reporting the anterior segment optical coherence tomography (ASOCT) findings of iris granuloma in this case. FINDINGS: Skin biopsy revealed plenty of acid fast bacilli with a bacteriological index of 5 suggestive of multibacillary polar lepromatous leprosy. ASOCT revealed well-demarcated smooth-surfaced nodular lesion with internal hyporeflectivity corresponding to the areas of granuloma which decreased in size following treatment with antileprosy drugs and systemic and topical steroids. CONCLUSION: ASOCT is a non-invasive technique to assess the extent of involvement of anterior segment in Hansen's disease and is a useful tool in follow-up. This is also the first report on ASOCT findings of iris granuloma in Hansen's disease.